4D temperature measurements using tomographic two-color pyrometry - Yu, Tao; Bauer, Florian; Huber, Franz; Will, Stefan; Cai, Weiwei (Optics Express, 2021)
This work presents a new approach for high-speed four-dimensional (3D+t) thermometry using only two high-speed cameras which are equipped with different band pass filters to capture thermal radiation signals at two narrow wavelength bands. With the help of a customized fiber bundle and a beam splitter, a total number of nine projections at each band were recorded, and the temperature distribution was evaluated by tomographic two-color pyrometry. In order to validate the effectiveness of this method, the 3D temperature distribution of a premixed steady flat flame was evaluated. The determined temperatures were compared to those of other studies, as well as to the results from inverse Abel transform and line-of-sight data. Further, the 3D temperature evolution of a weakly turbulent diffusion flame was observed at a repetition rate of 7.5 kHz. Such 4D temperature measurements are expected to be valuable in understanding turbulent combustion mechanisms especially of practical device